PENGARUH BIDANG DISKONTINUITAS TERHADAP KESTABILAN LERENG TAMBANG STUDI KASUS : LERENG HIGHWALL PIT’X’ PT. BERAU COAL - Al Kautsar, Muhammad Ilham; Khoirullah, Nur; Hendarmawan, Hendarmawan; Umboro, Sindhu (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2023)
Berau Coal is a company that currently manages open-pit coal mines, requiring geotechnical analysis. The purpose of this research is to determine the stability of slopes with and without discontinuities to understand the influence of discontinuity planes on the slopes. The method used involves classifying rock strength based on the Geological Strength Index (Marinos, 2007). In the research area, the GSI classification for sandstone and claystone ranges from <42 to >42, including classes III, IV, V, and X. Kinematic analysis, limit equilibrium analysis, and stereogram analysis are also conducted to determine the factor of safety.Based on kinematic analysis to determine the type of landslide (Wyllie & Mah, 2004), there can be a wedge failure in the highwall area. Limit equilibrium analysis is performed under two conditions: with the presence of discontinuity planes, yielding a factor of safety (FS) value of 1.636, and without the presence of discontinuity planes, yielding an FS value of 1.365. Meanwhile, the stereogram analysis yields an FS value of 3.4. In this case study, the FS value is higher when there are discontinuity planes compared to the condition without discontinuity planes. This is because the existing discontinuity planes intersect the critical slope, causing a change in the sliding plane direction towards the discontinuity plane.